Whole-exome sequencing identified a novel heterozygous variant in UBAP2L in a Chinese family with neurodevelopmental disorder characterized by impaired language, behavioral abnormalities, and dysmorphic facies - Yang, Qi; Zhang, Qiang; Zhou, Xunzhao; Feng, Juntan; Zhang, Shujie; Lin, Li; Yi, Shang; Qin, Zailong; Luo, Jingsi (Frontiers in Genetics, 2024)
UBAP2L-deficiency syndrome, also known as neurodevelopmental disorder with impaired language, behavioral abnormalities, and dysmorphic facies (NEDLBF, OMIM 620494), is an extremely rare autosomal dominant disorder. This condition is caused by heterozygous variant in the UBAP2L gene (NM_014847.4, MIM 616472), which encodes the ubiquitin-associated protein 2-like protein involved in the formation of stress granules (SGs). To date, only one report has documented 12 loss-of-function variants in UBAP2L, all of which were identified as de novo variants. In our study, we recruited a Chinese family with two patients exhibiting intellectual disability and seizures. Whole-exome sequencing was performed on the proband, revealing a novel heterozygous frameshift variant, UBAP2L (NM_014847.4):c.2453_2454del (p.Tyr818Trpfs*3). The variant was inherited from the affected mother, and confirmed in the proband and his parents by Sanger sequencing. This is the first familial report of a deleterious UBAP2L variant. The proband in this family presented a clinical phenotype similar to NEDLBF, which includes intellectual disability, developmental delay, speech delay, facial dysmorphism, seizures, and behavioral abnormalities. The affected mother presented only mild intellectual disability and mild language impairment. By clinical evaluation of our patients and previously reported cases with UBAP2L variants, we propose that intellectual disability, developmental delay (particularly in speech), infants’ feeding difficulties, behavioural abnormalities and seizures are the main clinical features of NEDLBF patients. Our study expands the genetic and phenotypic spectrum associated with NEDLBF.